Addiction to social networks, academic procrastination and family satisfaction in high school students in private Adventist educational institutions, in the San Martin region, during the health emergency, 2021 - Araujo Morales, Luz Victoria (2022)
Objective: to determine if there is a significant relationship between addiction to social networks,academic procrastination and family satisfaction in high school students in private Adventist educationalinstitutions in the San Martín region, during the health emergency, 2021. Methodology: Nonexperimentaldesign of a descriptive correlational type, cross-sectional study with a population of 500high school students from 4 private Adventist institutions in the city of Tarapoto of both sexes betweenthe ages of 12 and 18, to whom the Social Networks Addiction Scale, Academic Procrastination Scale,and Social Media Scale were applied. family satisfaction – FSS. Results: The results showed thatthere is a significant relationship between addiction to social networks and academic procrastination(R= 0.108; p<0.016). In the same way, in the results obtained, it was possible to show that there is asignificant relationship between the use of social networks and family satisfaction (-0.093*; p>0.039).Conclusion: There is a significant relationship between addiction to social networks and academic procrastination, in the same way, it was possible to show that there is a significant relationship betweenthe use of social networks and family satisfaction, that is, the greater the use of social networks, thegreater probability of showing procrastination and greater negative effects on family satisfaction.